Comparative analysis of preoperative and postoperative nasal appearance following unilateral complete cleft lip repair in Kano - Bardi M; Adebola RA; Efunkoya AA; Omeje KU; Amole IO; Suleiman AR; Bawa TA (Ibom Medical Journal)
Background: Cleft of the lip even after primary repair is reported to show residual deformities especially affecting the nose. The correction of nasal asymmetry is believed to be most challenging and has contributed greatly to modifications and improvement in surgical techniques. The aim of this study was to evaluate the nasal outcome using the symmetry of the nose in children with unilateral complete cleft lip following primary repair in Kano.